2020
DOI: 10.1055/a-1298-8121
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence, Machine Learning and Calculation of Intraocular Lens Power

Abstract: Background and Purpose In the last decade, artificial intelligence and machine learning algorithms have been more and more established for the screening and detection of diseases and pathologies, as well as for describing interactions between measures where classical methods are too complex or fail. The purpose of this paper is to model the measured postoperative position of an intraocular lens implant after cataract surgery, based on preoperatively assessed biometric effect sizes using techniques of machine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…In the present paper we describe the strategy of intraocular lens power calculation using the Castrop formula as described in Materials and Methods. The large dataset of 1452 eyes was split into training and test subsets [ 25 ]. The training data were used for formula constant optimization, and the test data for cross validation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present paper we describe the strategy of intraocular lens power calculation using the Castrop formula as described in Materials and Methods. The large dataset of 1452 eyes was split into training and test subsets [ 25 ]. The training data were used for formula constant optimization, and the test data for cross validation.…”
Section: Discussionmentioning
confidence: 99%
“…For cross validation, the N = 1452 measurements were split randomly into a training set (70%, 1017 cases) and a test set (30%, 435 cases) [ 25 ]. For the training set, the constants for the Castrop formula (C, H, R), the SRKT (A), the Hoffer-q (pACD), the Holladay1 (SF), the simplified Haigis (a0) and Haigis formula with triplet optimization (a0/a1/a2) were optimized in terms of minimizing the rmsPE using the nonlinear Levenberg-Marquardt algorithm [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…With repeated random subsampling, a random partition is separated out before calculation of the formula constant and this separated dataset then used for validation of the formula constant. However, this carries the risk that some data points may never be included in the training or validation data sets [10].…”
Section: Introductionmentioning
confidence: 99%
“…12 Langenbucher and coworkers attempted to model the measured postoperative position of an intraocular lens implant after cataract surgery using machine learning techniques. 42 Based on preoperative effect sizes of AL, corneal thickness, internal ACD, LT, mean corneal radius, and corneal diameter, 17 machine learning algorithms were tested for prediction performance for calculation of internal anterior chamber depth (AQD post) and axial position of the equatorial plane of the lens in the pseudophakic eye (LEQ_post). In terms of root mean squared error for AQDpost and LEQpost prediction, the Gaussian Process Regression Model with an exponential kernel outperformed the machine learning algorithms.…”
mentioning
confidence: 99%
“…Recent studies have shown that AI algorithms have the potential to exhibit comparable or higher accuracy compared to that of experienced clinicians. 42 Using rigorous validation approaches, these AI applications might be To date, only a few clinical trials have compared the efficacy of AI systems in real-world settings.…”
mentioning
confidence: 99%